Pengaruh Customer Relationship Management (CRM) terhadap Loyalitas Pelanggan Dengan Kepuasan Kerja sebagai Variabel Moderat - Titin Trimintarsih (Universitas Islam Kadiri, 2023)
Relationships with customers is more important than setting sales goals. Customer Relationship Management is one way to satisfy and retain loyal customers, and this method will be applied in research for businessman in Kampung Tahu Kota Kediri. The reason for choosing a location in Kampung Tahu that there are approximately 30 more businessman who have the same product, with the same location, so that the level of competition in Kampung Tahu is very tight and must avoid customer grabs, negative impacts. This research focused on the tofu industry house